Effects of Social Housing Changes on Immunity and Vaccine-Specific Immune Responses in Adolescent Male Rhesus Macaques - Pahar, Bapi; Baker, Kate C.; Jay, Alexandra N.; Russell-Lodrigue, Kasi E.; Srivastav, Sudesh K.; Aye, Pyone Pyone; Blanchard, James L.; Bohm, Rudolf P. (Frontiers in Immunology, 2020)
Nonhuman primates in research institutions may be housed in a variety of social settings for example group housing, pair housing or single housing based on the needs of research projects. Furthermore, housing may change over the course of studies. The effects of housing and changes in housing on cell activation and vaccine mediated immune responses are not well documented. We hypothesized that animals moved indoors from group to single housing (GH-SH) would experience more stress than those separated from groups into pair housing (GH-PH), or those placed briefly into pair housing and separated 5 weeks later into single housing (GH-PH-SH). We also compared the effects of separation from group to pair housing with the separation from pair to single housing. Eighteen male rhesus macaques were followed over the course of changes in housing condition over 10-14 weeks, as well as prior to and after primary vaccination with a commercially available measles vaccine. We identified two phenotypic biomarkers namely total CD8 population and proliferating B cells that differed significantly across treatment groups over time. At 10 weeks post separation, levels of proliferating B cells were higher in GH-SH subjects compared to GH-PH subjects, and in the latter, levels were lower at 10 weeks than prior to removal from group housing. At 2 weeks separation from group to single housing, the frequency of CD8+ T-cells were higher in GH-SH subjects compared to one week following the separation from pair into single housing in the GH-PS-SH subjects. Activated CD20 populations were persistently higher in the GH-SH animals that the GH-PH-SH animals, comparing the same elapsed time since the most recent separation. Housing configuration did not influence vaccine-mediated responses. Overall, our study found benefits of pair housing over single housing, suggest that perturbations in immune function will be more severe following separation from group to single housing than from pair to single housing, and support the use of short-duration pair housing even when animals must subsequently be separated. These findings are useful for planning the housing configurations of research nonhuman primates used for vaccine studies and other studies where immune response is being assessed.